UNVEILING VULNERABILITY: TRAUMA’S REFLECTION ON MASCULINITY IN MOONLIGHT (2016) AND KUCUMBU TUBUH INDAHKU (2018) - Anggriati, Sri Widia; Hidayatullah, Danial (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
This research aims to compare and investigate the trauma that affects men's masculinity in two different movies from America and Indonesia. This research compares two male characters who both experienced traumatic experiences but, in contrast, have different masculinities due to the influence of the trauma as well as the socio-cultural context they experienced. The objects of comparison for this research are the character Juno from the movie Kucumbu Tubuh Indahku (2018) and the character Chiron from the movie Moonlight (2016). The two characters share similarities in the causes of trauma, but they express different masculinities. To analyze this research, the comparative literature method, the theory of trauma by Levine (2008) and the theory of masculinity by R.W. Connell (2005) were used. The research results show that social-cultural influences play an important role in dealing with a person's trauma which can ultimately affect their masculinity. Juno does not receive social support from the people around him. He remains in subordinate masculinity. Meanwhile, Chiron, who received social support, experienced a change in his masculinity from subordinate masculinity to hegemonic masculinity.